Intravascular leiomyomatosis and benign metastasizing leiomyoma: an unusual case. Issue 3 (1st April 2006) - Arif, S.; Ganesan, R.; Spooner, D.
Abstract : Benign metastasizing leiomyoma (BML) and intravascular leiomyomatosis (IVL) are rare variants of uterine leiomyomas. In our search of available literature, there have been only two reports of these conditions occurring in the same patient. We report a case of a 42-year-old female presenting with a left L4 nerve root lesion, left paravesical lesion, left ovarian cyst, multiple pulmonary metastases, and an intracaval lesion. Histology confirmed these to be leiomyomata strongly positive for estrogen receptors. Treatment included surgery, in two stages, to remove the L4 nerve root, left paravesical lesion, intracaval lesion, and a single pulmonary nodule. The remaining tumor was treated with a gonadotrophin-releasing hormone agonist, resulting in significant reductions in tumor size. It was concluded that the lesions in the lungs were an example of BML arising from the initial diagnosis of uterine leiomyoma, and the caval lesion was an IVL. Long-term follow-up is recommended, and familiarity with rare forms of benign smooth muscle uterine tumors is essential in avoiding misdiagnosis and overtreatment.